Utopia, New Jersey : travels in the nearest Eden - Buchan, Perdita, 1940- (Book collections on Project MUSE., 2007)
Utopia. New Jersey. For most people?even the most satisfied New Jersey residents?these words hardly belong in the same sentence. Yet, unbeknown to many, history shows that the state has been a favorite location for utopian experiments for more than a century. Thanks to its location between New York and Philadelphia and its affordable land, it became an ideal proving ground where philosophical and philanthropical organizations and individuals could test their utopian theories. In this intriguing look at this little-known side of New Jersey, Perdita Buchan explores eight of these communities. Ad.